COST MANAGEMENT WITH APPLICATION OF ERP-SYSTEM TOOLS - O.V. Ponomarenko (Ukrainian Journal of Educational Studies and Information Technology, 2017)
The article investigates the problem of cost management in the ERP-systems. The developed application allows enterprises to reflect material, labour and financial costs. Assessment of costs in terms of money provides a measurable reflection of consumption of various resources by different activities.